Role of wind in erosion‐accretion cycles on an estuarine mudflat. Issue 1 (17th January 2017) - Shi, B. W.; Yang, S. L.; Wang, Y. P.; Li, G. C.; Li, M. L.; Li, P.; Li, C.
Abstract: Wind is an important regulator of coastal erosion and accretion processes that have significant ecological and engineering implications. Nevertheless, previous studies have mainly focused on storm‐generated changes in the bed level. This paper aims to improve the understanding of wind‐induced erosion‐accretion cycles on intertidal flats under normal (nonstormy) weather conditions using data that relates to the wave climate, near‐bed 3‐D flow velocity, suspended sediment concentration, and bed‐level changes on a mudflat at the Yangtze Delta front. The following parameters were calculated at 10 min intervals over 10 days: the wind wave orbital velocity (Ûδ ), bed shear stress from combined current‐wave action, erosion flux, deposition flux, and predicted bed‐level change. The time series of measured and predicted bed‐level changes both show tidal cycles and a 10 day cycle. We attribute the tidal cycles of bed‐level changes to tidal dynamics, but we attribute the 10 day cycle of bed‐level changes to the interaction between wind speed/direction and neap‐spring cyclicity. We conclude that winds can significantly affect bed‐level changes in mudflats even during nonstormy weather and under macro‐mesotidal conditions and that the bed‐level changes can be predicted well using current‐wave‐sediment combined models. Key Points: Normal wind also plays an important role in erosion‐accretion cycles even during nonstormy weather Variations in suspended sediment concentration is caused by the interaction of wind and tides Intratidal bed‐level changes can be predicted using current‐wave‐sediment models